Participating in on-the-spot first aid, outcome and influencing factors of the participation: an online survey among inpatients in Hunan province - Xi PENG; Zeya SHI; Zhijing LIU; Yan ZHANG; Shuhui YIN; Yanni LIANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the participation in on-the-spot first aid among inpatients in Hunan province and the outcome and influencing factors of the participation for providing a reference to improve pre-hospital emergency and field rescue.MethodsUsing stratified random sampling and a self-designed questionnaire, an online survey was conducted among 6 004 inpatients in 109 medical institutions in Hunan province during January - February 2022. The information on the inpatients' participation in on-the-spot first aid, the outcomes and influencing factors of their participations were collected and analyzed. Unconditional multivariate logistic regression model was used to explore influencing factors for outcomes of the on-the-spot first aid actions.ResultsFor the 5 964 inpatients finally included in the analysis, 1136 (19.05%) reported ever encountering on-site rescue events. Among the 1136 inpatients ever encountering on-site rescue events, 440 (38.73%) had participated in on-site rescue. Of the 440 participants taking on-site rescue, 71.86% called emergency services; 24.42% sent the first aid recipients to hospital; 12.79% performed cardiopulmonary resuscitation; and 2.56% conducted electric defibrillation. For all the first aid recipients in the on-the-spot first aids being involved by the inpatient participants, 213 (48.41%) were cured, 127 (28.86%) were improved, 75 (17.05%) died, and 25 (5.68%) had an unknown outcome. The results of unconditional multivariate logistic regression analysis showed that emergency personnel not arriving at the first aid site within 10 minutes was a hindering factor for the outcomes of the latest on-the-spot first aid; ever participating in on-the-spot first aid more than 3 times and emergency personnel arriving at the first aid site within 30 minutes were promoting factors for the outcomes of the latest on-the-spot first aid.ConclusionThe participation of on-the-spot first aid was low among inpatients in Hunan province. The outcome of the resued persons for the latest on-the-spot first aid being involved by the inpatient participants was mainly influenced by the time of emergency personnel arriving at the first aid site and the frequency of inpatients' ever participating in on-the-spot first aid.